Hydrogel applications: a promising frontier in pneumonia therapy - Wang, Junming; Wang, Pengfei; Liao, Kehan; He, Daikun (Frontiers in Bioengineering and Biotechnology, 2025)
Pneumonia remains a significant global health challenge due to its high incidence, mortality rates, and the limitations of conventional therapies, such as antibiotic resistance and inefficient drug delivery. In recent years, hydrogels have emerged as a promising biomaterial platform for pneumonia treatment, offering exceptional biocompatibility, tunable physicochemical properties, and multifunctionality. This review comprehensively examines the recent advancements in hydrogel applications for pneumonia therapy. It focuses on their roles as drug delivery vehicles, anti-inflammatory agents, and facilitators of tissue repair and regeneration. Hydrogels enable targeted and sustained release of antibiotics, anti-inflammatory drugs, and bioactive molecules, enhancing local drug concentrations while minimizing systemic side effects. Their ability to mimic the extracellular matrix (ECM) supports lung tissue repair and regeneration, addressing the long-term complications of pneumonia, such as fibrosis. Additionally, hydrogels can be engineered to respond to specific physiological conditions, such as pH or enzyme activity, allowing for intelligent drug release profiles tailored to the pulmonary microenvironment. Despite these promising developments, challenges related to material safety, drug loading efficiency, and scalability of manufacturing processes must be addressed to facilitate clinical translation. This review highlights the therapeutic potential of hydrogels in pneumonia treatment and provides insights into future research directions, aiming to bridge the gap between laboratory innovations and clinical applications.